Bulk Ring-Opening Polymerization of ?-Caprolactone by Zeolitic Imidazolate Framework; Catalysis Letters; Vol. 149, iss. 8 - Naz Farah; Mumtaz Fatima; Chaemchuen Somboon; Verpoort F. V. K. Frensis Valter Kornelius (2019, 2019)
Title screen